Threats to the long-term existence of Eleocharis multicaulis (Sm.) Desv. exposed to vegetation succession in dune slacks near Białogóra (Kashubian Seacoast, northern Poland) - Herbichowa, Maria; Herbich, Jacek (Biodiversity: Research and Conservation, 2006)
Dynamic trends of Eleocharis multicaulis in wet dune slacks were determined on the basis of the present and historical differentiation of vegetation as well as local distribution and habitat conditions of the species. The results concern the only locality of the species in northern Poland, located far away east of its range limit. The total area covered by E. multicaulis and the number of species localities markedly decreased during the last ca. 60 years. The main reason for the disappearance of local stands of the species was the encroachment of Myrica gale thickets on the places previously occupied by phytocoenoses of herbaceous vegetation representing, among others, the class Litorelletea and the association Eleocharitetum multicaulis. The persistence of Eleocharis multicaulis individuals is favoured by the oligotrophic character of the site and the stable, high water level. For long-term existence of the species at the investigated site, its active conservation will probably be required.